Analysis and Implementation of Raspberry Pi Based Wireless Access Point and User Access Notification Using Telegram - Pratama, Nashruddin Putra; Oktiawati, Unan Yusmaniar (Department of Electrical Engineering and Informatics, Vocational College, Universitas Gadjah Mada, 2022)
Internet network technology has become a human need in almost every activity. Communities in areas experiencing a lack of fiber optic network infrastructure need a tool to access the internet that can be used together in an affordable and efficient manner. This study tries to provide a solution to these problems. Raspberry Pi-based Wireless Access Point uses a USB modem which functions to build a Wireless Local Area Network. Then, a network quality test is carried out by calculating QoS on network traffic including packet loss, throughput and latency with scenarios based on a distance of 0 meter, 4 meter and 8 meter between the Wireless Access Point and the client by conducting online meetings and video streaming. Furthermore, to make it easier to monitor the Raspberry Pi device that acts as a Wireless Access Point, it will send user information that is connected via the Telegram bot.